UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA KOMPETENSI MENENTUKAN KOSA KATA TENTANG PERISTIWA SIANG DAN MALAM DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE NON-EXAMPLE PADA SISWA KELAS I SDN BERANGAS 1 KECAMATAN ALALAK - Marliana Noor (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
In the process of teaching and learning, there is often one direction of learning, thelearning media are not appropriate and then no variety of learningmethods, causing a lack ofstudent interest in learning and low completeness of learning outcomes.This research hasbeen conducted using the example non example learning method in two cycles, each cycle isdivided into two meetings with the percentage of teacher and student activity scores.Theresults showed that in the first cycle of the first meeting, the score of teacher and studentactivity respectively obtained 66.7% with a fairly good category and 63.6% of students beingactive. At the second meeting, the results obtained were 70.8% in the good category and68.2% of the students were active. In the second cycle, there was an increase in the scorecompared to the first cycle, the second cycle of the first meeting had an increase of 77.1% inthe very good category and 75% of the students were active. At the second meeting it reached85.4% in the very good category and 81.8% of students were active.The results showed thatthe method used was very effective in increasing student activity and improving Indonesianlearning outcomes on the competence of determining vocabulary about day and night events.